Important Things to Know about Medicare: Chapter One--Who Is Eligible for Medicare, and Do I Have To Sign Up for It? - Amanda Terminello; Martie Gillen (EDIS, 2014)
Important Things to Know about Medicare is a series of 10 publications that will cover the most common Medicare concerns. The series will provide general information about Medicare, including the four major plans, supplemental policies, interactions with different types of insurance, and assistance programs.